Determinación sérica de proteínas totales y su relación con su estado nutricional en adultos de ambos sexos del sector Virgen del Socorro del distrito La Esperanza - Trujillo enero 2013 - Marquina Castellanos, Cinthia Elena (2014)
In the present investigation disclosed the results of the determination of the seric level of total proteins on 90 adults of both sexes of the Human Settlement Virgin of Succor district of La Esperanza in January 2013; between the ages 18-60 years, were taken the respective blood samples and were submitted to analysis by the Biuret method, analyzing the relationship that exists between the serum level of total proteins and nutritional status, according to sex and age, using for this, statisticians for nominal data (percentages) and Chi Square for validation. The 85.6% of adults of both sexes, obtained normal seric level of total proteins, the 12.2% decreased level, while 2.2% obtained increased level. The higher prevalence of pre-obesity and obesity it has the females with a 52.4% and 17.5% respectively compared with the male sex with a 44.4% and 14.8% of pre-obesity and obesity respectively. In as to the age, was found a slightly higher percentage of obese people in the group of 41-60 years (17.8%) than in the group of 18-40 years (15.6%). According to statistical analysis, was found significant relationship between the serum level of total proteins and their nutritional status for female persons, as well as for persons of 18-40 years of age, with a significance level p <0.05